Paranoid Park - Nelson, Blake 1960- (Viking, 2006)
A sixteen-year-old Portland, Oregon skateboarder, whose parents are going through a difficult divorce, is engulfed by guilt and confusion when he accidentally kills a security guard at a train yard
Keywords: Guilt / Juvenile fiction; Skateboarding / Juvenile fiction; Murder / Juvenile fiction; Conduct of life / Juvenile fiction; High schools / Juvenile fiction; Schools / Juvenile fiction; Guilt / Fiction; Skateboarding / Fiction; Murder / Fiction; Conduct of life / Fiction; High schools / Fiction; Schools / Fiction; Inlineskating; Clique; Tödlicher Unfall; Illegalität; Inter-Gruppenkonflikt; Portland (Or.) / Juvenile fiction; Portland (Or.) / Fiction; Jugendbuch